(untitled) (Anwer Khan Modern Medical College Journal, 2021)
Introduction: Lung cancer alone and in coalition can deactivate life-wheel. But a very little attention had been paid to address the riddle. This effort is to candle the light on the lung cancer disease. Objective: This study was conducted to delineate the sociodemographic factors and clinical conditions of lung cancer patients. To determine some associations of SD variables and clinical conditions. Methods & Materials: This cross-sectional study was conducted in NICRH from July 2017 to June 2018 among 167 LC patients. Data were collected by interview using semi-structured questionnaire and reviewing of check list. Data were checked thoroughly, edited, coded, categorized, cleaned and analyzed using software (SPSS version 23). Results: This study revealed that mean age of the patients was 56.16 ± SD 9.88. Among which 80.2% were male and 19.8% female. Majority had primary 51.1% education Secondary were 26.4%. Regarding occupation, farmer were 37.1%, businessmen were 20.4% and homemaker were 15.6. The mean income was Tk. 17163 ± SD Tk. 10587. Most had nuclear family 89.2%. Rural inhabitants were 61.1%. In describing cancer type, 81.5% had NSCC and 16.8% had SCC. Regarding clinical condition, 70% had poor, 7.8% had average and 22.2% had severe clinical condition. The residential areas are significantly (χ2, p < .05) associated with clinical conditions. Staging of lung cancer is significantly (χ2, p < .05) associated with clinical conditions. Conclusion: Socioeconomic factors like age, family income, education, residential condition may affect clinical condition. AKMMC J 2022; 13(1) : 37-41